КУЛЬТУРАЛЬНО-МОРФОЛОГИЧЕСКАЯ И БИОХИМИЧЕСКАЯ ХАРАКТЕРИСТИКА ШТАММОВ ЛАКТОБАКТЕРИЙ, ВЫДЕЛЕННЫХ ИЗ ШУБАТА ВЕРБЛЮДОВ ЗАПАДНОГО КАЗАХСТАНА - Б. Кадралиева; Р. Мыктыбаева; A. Оразов; Б. Рыскалиева; Л. Надточий; М. Оразалиева (Animal Health and Biosafety, 2026)
The study focused on the isolation of new strains of lactobacilli from shubat obtained from Bactrian and Dromedary camels bred in the West Kazakhstan region. The aim of the study was to investigate the morphological, cultural, and biochemical properties of the isolated microorganisms in order to assess their biotechnological potential and suitability for use in the dairy industry. The results of the study revealed that all the isolated strains belong to the group of lactic acid bacteria of the genus Lactobacillus. Morphological analysis showed that the cells were gram-positive, non-motile, short rods arranged singly, in pairs, or in short and long chains. The cells ranged in size from 2,5 to 3,3 × 0,9 μm. However, the Sh-08L strain exhibited elongated cells reaching 6,0–8,0 μm, indicating the presence of intra-group morphological variability among the isolates. The cultural properties of the studied strains were characterized by the formation of colonies typical of lactic acid bacteria, which were grayish-white in color, convex in shape, with a smooth or moderately rough surface and an oily consistency. The isolates demonstrated stable growth under laboratory cultivation conditions and showed active acid formation in milk media, which is considered an important technological characteristic for starter cultures. Biochemical studies revealed a high level of metabolic activity of the isolated cultures. All strains actively fermented a wide range of carbohydrates, including glucose, galactose, lactose, sucrose, maltose, mannitol, and fructose, confirming their ability to efficiently utilize different carbon sources. At the same time, the studied isolates did not ferment pentoses such as arabinose and xylose and did not possess the ability to hydrolyze starch or utilize glycerol. In addition, the strains did not produce gas from glucose, indicating a homofermentative type of metabolism typical for technologically valuable lactobacilli. The obtained results indicate that the studied cultures belong to homofermentative lactic acid bacteria of the genus Lactobacillus and confirm their promising potential for use as components of starter cultures in the production of functional fermented dairy products with improved technological and probiotic properties.